2012
DOI: 10.1029/2011wr011586
|View full text |Cite
|
Sign up to set email alerts
|

Climate and vegetation controls on the surface water balance: Synthesis of evapotranspiration measured across a global network of flux towers

Abstract: [1] The Budyko framework elegantly reduces the complex spatial patterns of actual evapotranspiration and runoff to a general function of two variables: mean annual precipitation (MAP) and net radiation. While the methodology has first-order skill, departures from a globally averaged curve can be significant and may be usefully attributed to additional controls such as vegetation type. This paper explores the magnitude of such departures as detected from flux tower measurements of ecosystem-scale evapotranspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
249
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(270 citation statements)
references
References 74 publications
16
249
1
4
Order By: Relevance
“…Among the major findings reported here we found that the geographic variation in AET/MAP is mainly controlled by the climate patterns in China, while no significant differences were observed across vegetation types (Figure 2). Generally, forests are expected to evaporate and transpire a larger fraction of MAP than that of grasslands, because of their deeper and more extensive root systems, and higher leaf area and associated higher interception capacity (Williams et al, 2012). However, on the contrary, our results indicated that grasslands (0.92) generally had larger AET/MAP values than forests (between 0.60 and 0.74) (Figure 2a), which agreed with the global synthesis results of Williams et al (2012).…”
Section: Aet and Aet/map In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Among the major findings reported here we found that the geographic variation in AET/MAP is mainly controlled by the climate patterns in China, while no significant differences were observed across vegetation types (Figure 2). Generally, forests are expected to evaporate and transpire a larger fraction of MAP than that of grasslands, because of their deeper and more extensive root systems, and higher leaf area and associated higher interception capacity (Williams et al, 2012). However, on the contrary, our results indicated that grasslands (0.92) generally had larger AET/MAP values than forests (between 0.60 and 0.74) (Figure 2a), which agreed with the global synthesis results of Williams et al (2012).…”
Section: Aet and Aet/map In Chinamentioning
confidence: 99%
“…Generally, forests are expected to evaporate and transpire a larger fraction of MAP than that of grasslands, because of their deeper and more extensive root systems, and higher leaf area and associated higher interception capacity (Williams et al, 2012). However, on the contrary, our results indicated that grasslands (0.92) generally had larger AET/MAP values than forests (between 0.60 and 0.74) (Figure 2a), which agreed with the global synthesis results of Williams et al (2012). This is because that grasslands in China mainly locate in the temperate continental and alpine climate zones, and forests mainly locate in the monsoon climate zones, while AET/MAP of temperate continental and alpine climate zones tended to be larger than that of monsoon climate zones (Figure 2b).…”
Section: Aet and Aet/map In Chinamentioning
confidence: 99%
“…Due to different watersheds having totally different characteristics from one another regardless of how close they are, they will have different impacts on the streamflow resulting from changes in their forest coverage. Therefore, the impact of forests on the streamflow depend (to a greater or lesser extent) on several factors such as: the size of the watershed; the use of the soil being replaced by the forest; the fraction of the replaced area; the management, soil types and their properties (essentially their infiltration, transmission and water retention capacities); the depth of the water table; the spatial conformation of land uses in the river basin; climatic and meteorological characteristics prevailing in the region; climate changes; the topography of the land and other morphometric characteristics of the watershed (Farley et al, 2005;Oudin et al, 2008;Peel, 2009;Komatsu et al, 2010;Williams et al, 2012;Ferraz et al, 2013;Salemi et al, 2013). Based on the abovementioned for the present study, most of the nonsignificant results found may be due to a balance between variations in infiltration and ET variations, resulting in little influence of the forests on the streamflow.…”
Section: Relationship Of the Streamflow With Forest Coverage And Precmentioning
confidence: 99%
“…Most of these studies have been applied at single basins (Donohue et al, 2011;Jiang et al, 2015;Liang and Liu, 2014;Liu and McVicar, 2012;Roderick and Farquhar, 2011;Xu et al, 2014;Zhang X. et al, 2014) or multiple basins within a single region: USA (Chen et al, 2013;Wang and Hejazi, 2011;Carmona et al, 2014;Istanbulluoglu et al, 2012), Australia (Donohue et al, 2010(Donohue et al, , 2012Teng et al, 2012), China (Yang D. et al, 2007(Yang D. et al, , 2009Yang and Yang, 2011;Yang H. et al, 2014;Cong et al, 2015;Xiong and Guo, 2012;Yu et al, 2013) and Europe (Velde et al, 2014;Oudin et al, 2008). The global scale studies have also been conducted but mainly focusing on the development of the Budyko functional forms (Koster and Suarez, 1999;Zhang L. et al, 2001;Arora, 2002) and their parameters (Li et al, 2013;Williams et al, 2012).…”
Section: Introductionmentioning
confidence: 99%